Effect of oxygen deficiency on the excited state kinetics of WO(3) and implications for photocatalysis - Sachs, Michael (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Oxygen vacancies are widely used to tune the light absorption of semiconducting metal oxides, but a photophysical framework describing the impact of such point defects on the dynamics of photogenerated charges, and ultimately on catalysis, is still missing. We herein use WO(3) as a model material and investigate the impact of significantly different degrees of oxygen deficiency on its excited state kinetics. For highly oxygen-deficient films, photoelectron spectroscopy shows an over 2 eV broad distribution of oxygen vacancy states within the bandgap which gives rise to extended visible light absorption. We examine the nature of this distribution using first-principles defect calculations and find that defects aggregate to form clusters rather than isolated vacancy sites. Using transient absorption spectroscopy, we observe trapping of photogenerated holes within 200 fs after excitation at high degrees of oxygen deficiency, which increases their lifetime at the expense of oxidative driving force. This loss in driving force limits the use of metal oxides with significant degrees of sub-stoichiometry to photocatalytic reactions that require low oxidation power such as pollutant degradation, and highlights the need to fine-tune vacancy state distributions for specific target reactions.